Ferramenta para análise custo-efetividade no tratamento das úlceras venosas - Aron, Suzana [UNIFESP] (2017)
Introduction: Venous ulcers (VUs) require long-term treatments, representing a serious problem for health systems. Cost-effectiveness analyzes can be time-consuming and costly. However, the creation of a tool can provide useful preliminary results to managers and health professionals. Objective: To develop a tool for cost-effectiveness analysis in the treatment of venous ulcers. Methods: Spreadsheets were constructed in Excel® for the collection and comparison of matched-paired data of patients from two different treatment groups. Formulas were inserted to calculate the mean total cost and effectiveness of treatment for each group, as well as the incremental cost-effectiveness ratio (ICER) between two groups. Published data from a study comparing the cost-effectiveness of compression treatments using elastic bandage (Tr1) and Unna’s boot (Tr2) were used to demonstrate the applicability of the tool. The usability of the tool was tested with nurses specialized in the area, using a questionnaire. Results: The created tool enables the analysis of cost-effectiveness between two groups of patients with VUs who received different treatments, using retrospective and prospective data. In the demonstration of its applicability, the tool showed that Tr1 had a lower cost and lower effectiveness compared with Tr2 after 13weeks of treatment. The ICER was R$5,543.20 per additional reduction in Tr1. The tool was considered useful for decision making by all nurse who participated in the usability test. Conclusion: A tool was developed for cost-effectiveness analysis in the treatment of venous ulcers.